1978
DOI: 10.1002/aja.1001520307
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic observations of vaginal development in untreated and neonatally estrogenized balb/c Crgl mice

Abstract: Light and electron microscopic examinations of developing Mullerian vaginae were performed on untreated and neonatally estrogenized mice 1 to 12 days old. Vaginae of 1-day-old mice have a n undifferentiated, pseudostratified columnar epithelium which slowly differentiates in untreated mice into an apparently mucus-secreting epithelium. By day 12 the rough endoplasmic reticulum (RER), Golgi, and secretion granules are poorly developed features of the apical epithelial cells. In contrast, the stromal cells devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…One potential explanation is differential growth of Müllerian versus urogenital sinus epithelia, with UGE out-competing Müllerian epithelium. Another possibility may involve differential adhesion of basal epithelial cells of Müllerian versus urogenital sinus origin to the epithelial basement membrane mediated via hemidesmosomes (Cunha et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation is differential growth of Müllerian versus urogenital sinus epithelia, with UGE out-competing Müllerian epithelium. Another possibility may involve differential adhesion of basal epithelial cells of Müllerian versus urogenital sinus origin to the epithelial basement membrane mediated via hemidesmosomes (Cunha et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrastructural changes in the vaginal epithelium of neonatally estrogenized mice have been reported by Takasugi and Kamishima [1973] and Cunha et al [1978], but no such changes have been reported in neonatally androgenized mice. The present experi ments, therefore, were designed to study ultrastructural changes occurring during the development of perma nently altered vaginal epithelium in neonatally androgenized mice.…”
Section: Introductionmentioning
confidence: 96%
“…In particular, cell proliferation and differentiation of female reproductive organs, such as mammary gland, uterus and vagina, are tightly regulated by estrogens (1). In vagina, estrogens induce epithelial cell proliferation in the basal layer (2). The suprabasal cells are no longer mitogenic and differentiate while moving up through the epithelium (2).…”
mentioning
confidence: 99%
“…In vagina, estrogens induce epithelial cell proliferation in the basal layer (2). The suprabasal cells are no longer mitogenic and differentiate while moving up through the epithelium (2). The apical cells exhibit keratinization, and they lose their nuclei and cytoplasm, which are eventually shed from the surface (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation